Hysteresis gap-shrinking and structural effects of minor Al and Ti modifications on binary CuAl-based high-temperature shape memory alloys - Karaduman, Oktay; Ozkul, Iskender; Canbay, Canan Aksu (Iop Publishing Ltd, 2024)
Cu-based shape memory alloys (SMAs), except for exhibiting shape recovery, superelasticity, and high damping, are desirable because these smart materials have higher electrical and thermal conductivity and much lower prices than NiTi SMAs. However, they also have some downsides in mechanical strength and brittleness (mostly stemming from their coarse grain structure) and thermal instability. Therefore, adding some grain refining elements to these SMAs to improve their shape memory effect (SME), and thermal, structural, and mechanical properties is a widespread and simple way that significantly affects their martensitic phase transitions, structure, and mechanical properties. One of these grain-refining elements is titanium. Its thermal conductivity is lower than those of Cu and Al elements and has a low solubility in Cu-matrix. Besides the effects of small Al variations, the use of minor amounts of titanium in binary CuAl-base alloys can show impressive effects on all characteristics of these shape memory alloys, such as shape memory effect properties, martensitic transformation kinetics parameters, and microstructural features. In this research work, CuAlTi ternary high-temperature shape memory alloys (HTSMAs) with new compositions were produced by the arc melting method without a complicating use of Mn or Ni components in usual ternary CuAlMn and CuAlNi shape memory alloys. Thermal analyses of the prepared samples of the alloys were investigated by using differential scanning calorimetry (DSC) and differential thermal analysis (DTA) measurements. In contrast, x-ray diffraction (XRD) test results and optical micrographs were used for analyzing the structure of the alloy samples. The effect of different amounts of low soluble and grain refining Ti element on the binary CuAl alloy system was investigated.
Keywords: high temperature shape memory alloy; CuAlTi; DSC; DTA; Martensitic transformation; hysteresis gap